Use of Invasive Acacia Biomass to Produce Biochar and Solid Biofuels - Óscar González-Prieto; Luis Ortiz Torres (Applied Sciences)
This study focuses on the production of high-density solid biofuels and high-fixed-carbon biochar from two invasive acacia species harvested in a protected area in Northwestern Spain, thereby contributing to its silviculture management challenge. It is possible to transform the initial biomass into briquettes and pellets reaching high densified values above 1300 kg/m3 and 500 kg/m3, respectively. Using thermochemical conversion processes in a simple double chamber oven, a biochar was obtained with a fixed carbon of 66%. Several parameters were analyzed and compared between the original biomass and the resulting products. The results show that an added value could be achieved without applying a complex system to transform, starting from residual biomass from invasive species.